Alpha-Particle Emitting (213)Bi-Anti-EGFR Immunoconjugates Eradicate Tumor Cells Independent of Oxygenation - Wulbrand, Christian (Public Library of Science, 2013)
Hypoxia is a central problem in tumor treatment because hypoxic cells are less sensitive to chemo- and radiotherapy than normoxic cells. Radioresistance of hypoxic tumor cells is due to reduced sensitivity towards low Linear Energy Transfer (LET) radiation. High LET α-emitters are thought to eradicate tumor cells independent of cellular oxygenation. Therefore, the aim of this study was to demonstrate that cell-bound α-particle emitting (213)Bi immunoconjugates kill hypoxic and normoxic CAL33 tumor cells with identical efficiency. For that purpose CAL33 cells were incubated with (213)Bi-anti-EGFR-MAb or irradiated with photons with a nominal energy of 6 MeV both under hypoxic and normoxic conditions. Oxygenation of cells was checked via the hypoxia-associated marker HIF-1α. Survival of cells was analysed using the clonogenic assay. Cell viability was monitored with the WST colorimetric assay. Results were evaluated statistically using a t-test and a Generalized Linear Mixed Model (GLMM). Survival and viability of CAL33 cells decreased both after incubation with increasing (213)Bi-anti-EGFR-MAb activity concentrations (9.25 kBq/ml–1.48 MBq/ml) and irradiation with increasing doses of photons (0.5–12 Gy). Following photon irradiation survival and viability of normoxic cells were significantly lower than those of hypoxic cells at all doses analysed. In contrast, cell death induced by (213)Bi-anti-EGFR-MAb turned out to be independent of cellular oxygenation. These results demonstrate that α-particle emitting (213)Bi-immunoconjugates eradicate hypoxic tumor cells as effective as normoxic cells. Therefore, (213)Bi-radioimmunotherapy seems to be an appropriate strategy for treatment of hypoxic tumors.